The impact of environmental regulation on China’s industrial green development and its heterogeneity - Chen, Huangxin; Yang, Yuping; Yang, Mengting; Huang, Hao (Frontiers in Ecology and Evolution, 2022)
The research analyzes the impact of environmental regulation on industrial green development using panel data from 30 provinces in China from 2006 to 2018. We employ the Super-slack-based measuring (SBM) model to measure the level of domestic industrial green development and use the ordinary panel model, the panel threshold model, and the spatial panel model for empirical estimation. The results reveal that the environmental regulation index plays a significant role in promoting such development. Environmental regulation index, command-and-control environmental regulation, market-incentive environmental regulation, and public-participation environmental regulation all have only a single threshold of technological progress and fiscal decentralization. Further analysis shows that China’s industrial green development presents obvious spatial agglomeration characteristics, and there is a significantly positive spatial correlation between different environmental regulation indicators and industrial green development. Our findings provide useful policy recommendations for promoting industrial green development in China.